Pengembangan Sistem Waste Management berbasis Open-Source ERP - Navya Kirana Safitri; Ari Yanuar Ridwan; Umar Yunan Kurnia Septo Hediyanto; Rosad Ma’ali el Hadi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The leather processing industry is one of the industries with a high production level to meet market demand. This leather apparel company located in Garut, West Java, produces leather, both from cow, sheep, and goatskin as its raw material and manufactures leather-based apparel as its finished goods. Besides its primary production, this leather tanning company also produces hazardous wastewater that can pollute the environment due to chemical compounds in the leather tanning process. They do not have an integrated information system that supports their business processes, especially in controlling the waste management process. This research will design a waste management module ERP system that supports sustainable supply chain management. The use of ERP that supports integration with another element in the company will make it easier for companies to categorize the waste from the manufacturing process and stored it in the warehouse. Not only that, but this system also helps determine the amount of waste produced and whether the wastewater meets the wastewater quality standards, which are then reported in the document automatically, which will make it easier to analyze results and assist in further decision making.